Characterization of microwave generator energy and ablation volumes following transarterial embolization in an in vivo porcine liver model - Sparks, Hiro; Rink, Johann; Ramakrishnan, Abinaya; Sung, Kyunghun; Ni, Jason; Lu, David S. K.; Raman, Steven S.; Lee, Edward W.; Chiang, Jason (Journal of vascular and interventional radiology, 2024)
Purpose - To characterize the relationship between ablation zone volume (AZV) and microwave ablation (MWA) energy in an in vivo porcine liver model following arterial embolization. - Materials and Methods - With Institutional Animal Care and Use Committee (IACUC) approval, 11 female swine underwent either right (n = 5) or left (n = 6) hepatic artery embolization under fluoroscopic guidance. Subsequently, ultrasound (US)-guided MWA was performed in each liver segment (left lateral, left medial, right medial, and right lateral) at either 30 W (n = 4 lobes), 60 W (n = 4), 65 W (n = 20), 90 W (n = 8), 120 W (n = 4), or 140 W (n = 4) continuously for 5 minutes. Postprocedural volumetric segmentation was performed on standardized multiphase T1 magnetic resonance (MR) imaging sequences. - Results - Mean AZVs in embolized lobes (15.8 mL ± SD 10.6) were significantly larger than those in nonembolized lobes (11.2 mL ± SD 6.5, P < .01). MWA energy demonstrated significant positive linear correlation with both embolized (R2 = 0.66, P < .01) and nonembolized (R2 = 0.64, P < .01) lobes. The slope of the linear models corresponded to a 0.95 mL/kJ (SD ± 0.16) and 0.54 mL/kJ (SD ± 0.09) increase in ablation volume per applied kilojoule of energy (E) in embolized and nonembolized lobes, respectively. In the multivariate model, embolization status significantly modified the relationship between E and AZV as described by the following interaction term: 0.42∗E∗(embolization status) (P = .031). - Conclusions - Linear models demonstrated a near 1.8-fold increase in ratio of AZV per unit E, R(AZV:E), when applied to embolized lobes relative to nonembolized lobes. Absolute AZV differences between embolized and nonembolized lobes were greater at higher-power MWA.
Gesehen am 14.01.2025